Nectar of the wicked - Ella Fields (UK Hodderscape, 2024)
Forget morally grey - this is pitch black' NISHA J. TULI 'Sizzling' RAVEN KENNEDY A Court of Thorns and Roses meets Rapunzel in this spicy romantasy by bestselling author Ella Fields! For twenty years, I was an unwanted changeling with no name, no family, and no answers . . . That is until an irresistibly wicked faerie begins a seductive game. I am his prey. His treasure. He offers a trade: he will take me to the faerie realms to help me find the truth of who I am. In return, I must agree to marry him. But nothing is as it seems, and soon after arriving at his wintry manor, I begin to unravel a dangerous web of lies. Far deadlier still, I'm falling in love with a monster who has no heart. FEATURED TROPES: Enemies to lovers Marriage of convenience Fated mates Spicy READERS CAN'T GET ENOUGH 'One of my favourite fantasy auto-buy fantasy authors.' 'Once again, I am obsessed' 'Ella Fields coming in HOT, once again, my queen of filthy, smutty, plot-heavy romantasies' 'I stayed up till 3am to finish' 'I need to know what happens next!!!'
Keywords: English Literature